Monitoring the pulse arrival time using optical fibre sensors - Wan Zaki, Wan Suhaimizan (2020)
The plastic optical fibre (POF) is widely explored in various sensor applications. The non-toxic and biochemical inertness properties of the material make it safe to be applied on the human skin and hence opens up a wealth of wearable opportunities. To date, no one has investigated the combination of POFs and textile electrodes that are well suited to smart textile applications. Therefore, in this thesis, POFs were explored as an extrinsic sensor for the measurement of photoplethysmogram (PPG) on the human body. Further, a conductive textile electrode was utilized for Electrocardiogram (ECG) measurement. The ECG and the PPG signals were synchronized using a Nexus-10 MK II data acquisition device along with Matlab software for subsequent analysis. In this study, the delay time between the ECG and PPG are calculated and denoted as pulse arrival time (PAT). The PAT is grouped into three categories which depend on the position of the PPG signal measured at the finger (PPTf), wrist (PATw) and underfoot (PATt). A relationship between mean PAT (15 beats) and instantaneous PAT (a single beat) with blood pressure (BP) was investigated on thirteen healthy male volunteers (aged between 17 to 42 years) through a pedal exercise. A linear regression model was applied to mean/instantaneous PAT-BP data and the absolute correlation coefficient, ІrІ was determined on each volunteer. The results show that the PAT is well correlated with systolic BP, especially for PATf (instantaneous and mean PAT), with 100% of volunteers achieving ІrІ > 0.5. For PAT and diastolic BP correlation, majority of volunteers achieving ІrІ < 0.5 for all categories, PATf, PATw and PATt (instantaneous and mean PAT). Next, a new one-step calibration method and a pedal exercise calibration method were evaluated to estimate systolic BP during a tilt table experiment. The results show that the one-step calibration method at the finger show a marginally better correlation coefficient, (r = 0.65) compared to the pedal exercise calibration method (r = 0.45), when estimating systolic BP. Advantageously, the one-step calibration method is simple and time-saving because it only required one measurement of BP using a cuff-based BP monitor as a reference. Lastly, a tubular cardiovascular phantom system was proposed and developed to simulate the PDT measurement in a controlled environment. The results of the phantom study showed a similar pattern to the PTT in human model, thus indicating that the system is able to simulate the PDT for sensor validation purposes.